2006
DOI: 10.1080/10408440500541367
|View full text |Cite
|
Sign up to set email alerts
|

A Tiered Approach to Life Stages Testing for Agricultural Chemical Safety Assessment

Abstract: A proposal has been developed by the Agricultural Chemical Safety Assessment (ACSA) Technical Committee of the ILSI Health and Environmental Sciences Institute (HESI) for an improved approach to assessing the safety of crop protection chemicals. The goal is to ensure that studies are scientifically appropriate and necessary without being redundant, and that tests emphasize toxicological endpoints and exposure durations that are relevant for risk assessment. The ACSA Life Stages Task Force proposes a tiered app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(80 citation statements)
references
References 26 publications
0
77
0
3
Order By: Relevance
“…Non-linear TK, in which metabolism or excretion pathways available at lower blood concentrations are partly or fully saturated with increasing dose, may be a clear confounder both in appropriately designing toxicological studies and evaluating results for hazard and human risk assessment. Use of TK to inform human-relevant dose selection in animal toxicity studies has been affirmed in recent reviews and Organization for Economic Cooperation and Development (OECD) guidance on conduct of the EOGRT study Carmichael et al 2006;Cooper et al 2006;OECD 443, 2012a). The guidance recommended that top dose level(s) should not exceed the inflection point of onset of TK non-linearity if the inflection point dose was well separated from human exposures, and further concluded that toxicity limited to doses above the onset of non-linear TK behavior was not quantitatively relevant to human risk.…”
Section: Differentiating Potential Endocrine Modes Of Action Based Onmentioning
confidence: 99%
“…Non-linear TK, in which metabolism or excretion pathways available at lower blood concentrations are partly or fully saturated with increasing dose, may be a clear confounder both in appropriately designing toxicological studies and evaluating results for hazard and human risk assessment. Use of TK to inform human-relevant dose selection in animal toxicity studies has been affirmed in recent reviews and Organization for Economic Cooperation and Development (OECD) guidance on conduct of the EOGRT study Carmichael et al 2006;Cooper et al 2006;OECD 443, 2012a). The guidance recommended that top dose level(s) should not exceed the inflection point of onset of TK non-linearity if the inflection point dose was well separated from human exposures, and further concluded that toxicity limited to doses above the onset of non-linear TK behavior was not quantitatively relevant to human risk.…”
Section: Differentiating Potential Endocrine Modes Of Action Based Onmentioning
confidence: 99%
“…At present, the two-Generation Reproductive Toxicity study based on OECD TG 416 of 2001 is required in the respective Regulations. However, animal numbers for reproductive toxicity testing could be reduced by up to 50% compared to the two-Generation study by using the EORGTS (Cooper et al, 2006). Moreover, the EGORTS is designed to include additional endpoints (neurotoxicity, immunotoxicity, endocrine-mediated toxicity), which may further decrease the number of animals used for risk assessment.…”
Section: Data Evaluationmentioning
confidence: 99%
“…rabbit), if the reproduction study is conducted on another species (such as rat or mouse) (Hurtt et al, 2003;Cooper et al, 2006).…”
Section: Reproductive and Developmental Toxicity Testingmentioning
confidence: 99%